1983
DOI: 10.1002/ajmg.1320160115
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal or X‐linked recessive syndrome of congenital lymphedema, hypoparathyroidism, nephropathy, prolapsing mitral valve, and brachytelephalangy

Abstract: Two brothers were found to have an unusual congenital syndrome of lymphedema, pulmonary lymphagiectasia, hypoparthyroidism, hereditary nephropathy, prolapsing mitral valve, and other somatic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Other entities that should be considered are the lymphedema‐cholestasis (Aagenaes) syndrome [Aagenæs, 1998], autosomal recessive congenital chylothorax with edema developing in the first days of life [Williams and Josephson, 1997], congenital lymphedema in two brothers with unusual face and atrial septal defect [Irons et al, 1996], and congenital pulmonary lymphangiectasia without peripheral lymphedema and with hemidiaphragmatic eventration, very small mouth, and other dysmorphic features [Gilewski et al, 1996]. Congenital lymphedema may also be present in the autosomal dominant Milroy disease [Ferrell et al, 1998], distichiasis– lymphedema syndrome [Robinow et al, 1970], microcephaly–lymphedema syndrome [Crowe and Dickerman, 1986], hypoparathyroidism–nephropathy–lymphedema syndrome [Dahlberg et al, 1983], lissencephaly–cerebellar hypoplasia–lymphedema syndrome [Hourihane et al, 1993], velocardiofacial syndrome [Mansir et al, 1999], anhidrotic ectodermal dysplasia with immunodeficiency, osteopetrosis, and lymphedema [Doffinger et al, 2001], and Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Other entities that should be considered are the lymphedema‐cholestasis (Aagenaes) syndrome [Aagenæs, 1998], autosomal recessive congenital chylothorax with edema developing in the first days of life [Williams and Josephson, 1997], congenital lymphedema in two brothers with unusual face and atrial septal defect [Irons et al, 1996], and congenital pulmonary lymphangiectasia without peripheral lymphedema and with hemidiaphragmatic eventration, very small mouth, and other dysmorphic features [Gilewski et al, 1996]. Congenital lymphedema may also be present in the autosomal dominant Milroy disease [Ferrell et al, 1998], distichiasis– lymphedema syndrome [Robinow et al, 1970], microcephaly–lymphedema syndrome [Crowe and Dickerman, 1986], hypoparathyroidism–nephropathy–lymphedema syndrome [Dahlberg et al, 1983], lissencephaly–cerebellar hypoplasia–lymphedema syndrome [Hourihane et al, 1993], velocardiofacial syndrome [Mansir et al, 1999], anhidrotic ectodermal dysplasia with immunodeficiency, osteopetrosis, and lymphedema [Doffinger et al, 2001], and Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Dahlberg et al reported two brothers who also had lymphoedema, pulmonary lymphangiectasia, renal insufficiency, and prolapsing mitral valves. 8 Barakat et al reported two brothers who had hypoparathyroidism, nerve deafness, and steroid resistant nephrotic syndrome.9 A renal biopsy specimen taken from one of the boys revealed fetal like glomeruli. There are some similarities between these children and those reported here in that two of the children in our series had documented nerve deafness and fetal like glomeruli was seen at biopsy in case 2.…”
Section: Discussionmentioning
confidence: 99%
“…None of these resemble the current family either facially or in the spectrum of associated malformations. Case reports of lymphedema syndromes in association with a variety of abnormalities can be found in the published literature [Avasthey and Roy, 1968; Dahlberg et al, 1983; Doffinger et al, 2001]. To our knowledge none of these involved the neurodevelopmental abnormalities seen in our patients.…”
Section: Discussionmentioning
confidence: 62%